Pencapaian Hasil Belajar Biologi Dengan Problem Based Learning (PBL) dan Student TeamsAchievement Divisions (STAD) Ditinjau dari Minat Belajar Peserta Didik Sekolah Menengah Atas Negeri di Kabupaten Grobogan - Sigit Wirawan; Samsi Haryanto; Suharno Suharno (Universitas Sebelas Maret, 2016)
he objective of research was to find out: (1) how the application of ASSURE learning design model can improve mathematic learning motivation and achievement in the 4????ℎ grades of SD Negeri 01 Tlobo of Jatiyoso Sub District of Karanganyar Regency, (2) why the application of ASSURE learning design model can improve mathematic learning motivation and achievement in the 4????ℎ grades of SD Negeri 01 Tlobo of Jatiyoso Sub District of Karanganyar Regency, (3) how the effectiveness of ASSURE learning design model can improve mathematic learning motivation and achievement in the 4????ℎ grades of SD Negeri 01 Tlobo of Jatiyoso Sub District of Karanganyar Regency. This study was a classroom action research conducted in 3 cycles. Each of cycle consisted 0f 4 stages: planning, acting, observing, and reflecting. The subject of research was the 4????ℎ grades of SD Negeri 01 Tlobo consisted of 23 students. Techniques of collecting data used were learning achievement test, motivation, observation, interview, and experiment. Technique of analizing data used was an interactive model of analysis encompassing: data reduction, data display, and conclusion drawing. The results of classroom action research were as follows: (1) the application of ASSURE learning design model formulated learning objective, explained the material and the way of working on the exercises not in a hurry, used discovery and expository method, used laptop, LCD and CD learning media, fold paper, and color marker, and the implementation of mathematic learning procedure appropriately in Elementary school could improve motivation by 91,30% and learning achievement by 95,65%, (2) the advantage of ASSURE learning design model application was that teh students were very interested in learning using laptop, LCD and CD learning media, fold paper, and color marker. The students were interested in and challenged in assigning task in tke learning procedure of undertanding concept. Its disadvantages were that the students demonstrated fold paper shyly in the fraction arithmatic operation, the students took more time to work on exercise, and the students had not been fluent in simplifying the fraction, (3) considering the result of calculation, it could be found: ???????????????? = 2,55, while ???????????????????????? = 2,020, so that ???????????????? > ????????????????????????; therefore: the aplication of ASSURE learning designed model was used effectively for improving the mathematic learning motivation and achievement in the 4????ℎ grades of SD Negeri 01 Tlobo of Jatiyoso Sub District of Karanganyar Regency